Factors associated with low birthweight in Palestinian refugees at Al-Wehdat camp, Jordan: a cross-sectional study using routine data. (March 2019) - Aliabadi, Shirin; Hababeh, Majed; Kitamura, Akiko; Hajat, Shakoor
Abstract: Background: Low birthweight (LBW), defined as a birthweight of less than 2500 g, is a leading cause of infant morbidity and mortality worldwide. Previous studies have shown that the risk of LBW is higher in vulnerable populations, such as refugees. Few studies have assessed the prevalence and associated risk factors of LBW in refugee populations using routine monitoring data. This study sought to measure the prevalence of LBW and associated risk factors in refugees in Al-Wehdat Camp in Jordan using routine monitoring data. Methods: The study examined a dataset that included 3916 births from mothers registered in the UNRWA e-Health database between June 1, 2016, and June 30, 2017. The dataset was cleaned and variables were analysed. The variables were parity, mother's age, maternal education level, marital status, mother's occupation, multiple pregnancies, presence of complications, diastolic hypertension above 90 mm Hg, place of delivery, number of antenatal visits, sex of infant, infant year of birth, infant month of birth, and type of service received (family planning or antenatal services). Continuous variables were grouped into categorical (eg, parity, number of antenatal visits, mother's age) or binary variables (eg, infant's birthweight). Bivariable and multivariable logistic regression were employed to evaluate the association between previously identified potential risk factors and LBW outcomes. The resulting odds ratios (ORs) and adjusted ORs were evaluated. Findings: The prevalence of LBW was 6·3% (246 of 3916). In the crude analysis, significant associations were found between the presence of maternal complications (OR 2·86; 95% CI 2·02–4·04) with LBW outcomes. Significant associations were also found between women that did not receive full antenatal services (OR 1·36; 95% CI 1·03–1·78) and LBW outcomes. Multivariable analyses showed that LBW outcomes were higher with maternal complications (adjusted OR 2·85; 95% CI 2·10–4·24) and receipt of full antenatal services over receiving only family planning (1·37; 95% CI 1·04–1·81), when adjusting for the a priori confounders. Interpretation: The study identified positive associations between LBW outcomes and maternal complications and the type of health service received. No other associations were significant, but some variables confounded the relationship between maternal complications and LBW outcomes. The study supports findings from previous studies, such as an increased risk of LBW outcomes when maternal complications are coupled with no family planning. The implications of this study are that prevention of maternal complications should be improved and that there should be better care of women with such complications. In addition, family planning services should be available to all women. Further research is required to form robust policies to reduce the burden of LBW in the context of vulnerable Palestinian refugees. Funding: None.